2020
DOI: 10.1007/s00122-020-03697-8
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping and genomic selection for sorghum adaptation to tropical soils of Brazil in a sorghum multiparental random mating population

Abstract: Key message A multiparental random mating population used in sorghum breeding is amenable for the detection of QTLs related to tropical soil adaptation, fine mapping of underlying genes and genomic selection approaches. Abstract Tropical soils where low phosphorus (P) and aluminum (Al) toxicity limit sorghum [Sorghum bicolor (L.) Moench] production are widespread in the developing world. We report on BRP13R, a multiparental random mating population (MP-RMP), which is commonly used in sorghum recurrent selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…Of several sources of genetic male sterility, the ms3 and ms7 alleles have been extensively used in population improvement programs worldwide due to their stability across environments (Bhola, 1982 , Reddy and Stenhouse, 1994 ; Murty and Rao, 1997 ). Of late, Bernardino et al ( 2021 ) reported that a multiparental random mating population in sorghum could be used to detect QTLs related to tropical soil adaptation, fine mapping of underlying genes, and genomic selection approaches. Keeping the advantages of the population breeding in bringing together the desirable alleles, we initiated a population breeding approach in 2000 and the two populations were developed, one for female parent (B line) development and another for male parent (R) development.…”
Section: Introductionmentioning
confidence: 99%
“…Of several sources of genetic male sterility, the ms3 and ms7 alleles have been extensively used in population improvement programs worldwide due to their stability across environments (Bhola, 1982 , Reddy and Stenhouse, 1994 ; Murty and Rao, 1997 ). Of late, Bernardino et al ( 2021 ) reported that a multiparental random mating population in sorghum could be used to detect QTLs related to tropical soil adaptation, fine mapping of underlying genes, and genomic selection approaches. Keeping the advantages of the population breeding in bringing together the desirable alleles, we initiated a population breeding approach in 2000 and the two populations were developed, one for female parent (B line) development and another for male parent (R) development.…”
Section: Introductionmentioning
confidence: 99%
“…In the seedling stage is feasible to differentiate genotypes considering P acquisition efficiency, due to changes in root architecture and morphology under low-P (Sousa et al, 2012;Hufnagel et al, 2014;Bernardino et al, 2020Bernardino et al, , 2021. The use of appropriate phenotyping methods to analyze seedlings reduces cost and time in the selection of P-efficient genotypes (Van Eeuwijk et al, 2019).…”
Section: Sorghum Root System Phenotypingmentioning
confidence: 99%
“…A better understanding of how sorghum hybrids respond to P starvation is necessary to breed crops with enhanced P use efficiency traits (Hufnagel et al, 2014;Wen et al, 2019;Bernardino et al, 2020Bernardino et al, , 2021. Thus, this study aimed to identify and characterize hybrids regarding root traits related to P acquisition efficiency.…”
Section: Sorghum Root System Phenotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…In its turn, significant work was conducted The genomic prediction approach has been undergoing constant adjustments over the years. Many efforts have been allocated to applying genomic prediction to several crops, such as maize (Dias et al, 2020;Beyene et al, 2019), wheat (Juliana et al, 2020), rice (Labroo et al, 2021b), and sorghum (Oliveira et al, 2018;Bernardino et al, 2021), and to define the best prediction models and approaches (Santos et al, 2015;Dias et al, 2018;Fristche-Neto et al, 2018).…”
Section: Genotype-by-environment Interaction In Sorghummentioning
confidence: 99%